Implementation of the REAP Strategy in the Aqidah Akhlak Course to Improve Student Literacy Ability - Dzulfikar Akbar Romadlon; Doni Septi; Budi Haryanto (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
Aqidah Akhlak is a course that must be attended by PAI students because they will become teachers who will teach this course. The Aqidah Akhlak teacher requires the ability of